Animus Digitus: Rethinking the Human in Digital Anthropology Through Islamic Theology - Suhermanto Ja'far; Kunawi Kunawi (Sekolah Tinggi Agama Islam Sadra, 2026)
This article explores the conceptual transformation of human existence in the digital era through the debate between Homo Digitus and Animus Digitus within the framework of digital humanities and Islamic philosophical–theological anthropology. The main problem addressed in this study concerns the growing tendency toward reductionism in digital discourse, where human beings are increasingly understood as data entities, algorithmic functions, or objects of technological optimization. Such perspectives risk overlooking the dimensions of meaning, faith, and moral responsibility that constitute the core of human existence. This study employs a qualitative conceptual approach grounded in philosophical analysis, digital humanities perspectives, and Islamic theological reflection. The analysis compares the descriptive concept of Homo Digitus—which portrays humans as actors within digital socio-technological systems—with the normative–theological concept of Animus Digitus, which emphasizes humans as subjects endowed with soul, intention, and moral accountability in front of others, the environment, and God. The findings show that while Homo Digitus is analytically useful at the sociological level, it is insufficient to explain the ethical and spiritual dimensions of digital human life and the transcendental aspects that accompany it. The novelty of this research lies in the aspect of proposing the concept Animus Digitus as a normative–theological framework that integrates digital humanities with Islamic anthropology, thereby offering a more holistic interpretation of human existence in the digital age and provide an ethical basis for the development and use of digital technology that is oriented towards human dignity.